1970
DOI: 10.1039/j29700000588
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and mechanism of dimerisation of benzonitrile N-oxides to furazan N-oxides

Abstract: The rates of dimerisation of benzonitrile N-oxide and of some rnetaand para-substituted derivatives, leading to diarylfurazan N-oxides, have been measured. The rate increases in the order rn-CI > p-CI > H > p-Me > p-OMe, a Hammett-type relationship being obeyed (p = +0*86). The reaction rate is slightly affected by change of solvent; the reaction is faster by a maximum factor of ten in carbon tetrachloride t h a n in other more polar or better solvating media, such as chlorinated hydrocarbons, alcohols, dioxan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

1970
1970
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 0 publications
2
20
0
Order By: Relevance
“…Through the comparison of k and τ 1/2 values for aromatic NO s, we found that the electron‐donating group at the para ‐position facilitates the thermal isomerization. It is well known that the electron‐rich aromatics tend to easily migrate on the skeletal rearrangements , . Our observations are in a good agreement with the tendency of typical rearrangement reactions.…”
Section: Resultssupporting
confidence: 90%
“…Through the comparison of k and τ 1/2 values for aromatic NO s, we found that the electron‐donating group at the para ‐position facilitates the thermal isomerization. It is well known that the electron‐rich aromatics tend to easily migrate on the skeletal rearrangements , . Our observations are in a good agreement with the tendency of typical rearrangement reactions.…”
Section: Resultssupporting
confidence: 90%
“…This suggested that nitrile oxide intermediates are very possibly generated and involved in the present Pd/Mn‐catalyzed aerobic aldoxime dehydration reaction. To certify this hypothesis, nitrile oxide 5 a , obtained in situ by treating 3 a with trichloroisocyanuric acid according to the literature method, was then treated with 1 mol% Pd(OAc) 2 . As shown in Scheme , the reaction readily afforded 4 a in 42% yield.…”
Section: Catalyst Screening and Condition Optimization[a]mentioning
confidence: 99%
“…The rate of this dimerisation is exceptionally fast for lower aliphatic nitrile oxides, with acetonitrile oxide dimerising in less than one minute, whereas the half-life of most aromatic nitrile oxides at room temperature is several hours. 8,85 …”
Section: Scheme 12mentioning
confidence: 99%